Processing at-issue and non-at-issue content: Evoked and induced brain activities reveal early and long-lasting differences. - Anna Czypionka; Laura Reimer; Mariya Kharaman; Carsten Eulitz (PLoS ONE)
The processing of context-dependent expressions has mostly been studied using metaphors, irony or indirect requests. We add to the literature by monitoring the processing of modal particles (MPs) like German ruhig. These lexemes are ambiguous between a modal particle reading and a counterpart reading. While the counterpart contributes at-issue or propositional meaning to the sentence and affects truth conditions, the modal particle contributes non-at-issue meaning, expressing speaker attitudes or linking the sentence to the discourse. In the present study we disambiguated the readings via a preceding context and analysed event-related potentials and the oscillatory brain responses to critical sentences with identical surface forms. Our results show that in comparison to their counterparts, modal particles are associated with enhanced P600 amplitudes on the target lexemes and in the spillover region, and with enhanced P200 amplitudes on target lexemes. In addition, modal particles do not show the gamma power enhancement visible for counterparts. We interpret our findings as showing increased processing cost for modal particles due to them contributing to a higher dimension of meaning. The differences in oscillatory brain activity between both readings may reflect the lack of at-issue meaning contribution for modal particles. Our findings are in line with reports of enhanced P600 amplitudes for semantically and pragmatically complex readings in the literature on context-dependent expressions, and open various future ways of research to check the claims of different models on the processing of complex semantic and pragmatic information.